In God we trust? Neural measures reveal lower social conformity among non-religious individuals - Thiruchselvam, Ravi; Gopi, Yashoda; Kilekwang, Leonard; Harper, Jessica; Gross, James J. (Social cognitive and affective neuroscience, 2017)
Even in predominantly religious societies, there are substantial individual differences in religious commitment. Why is this? One possibility is that differences in social conformity (i.e. the tendency to think and behave as others do) underlie inclination towards religiosity. However, the link between religiosity and conformity has not yet been directly examined. In this study, we tested the notion that non-religious individuals show dampened social conformity, using both self-reported and neural (EEG-based ERPs) measures of sensitivity to others’ influence. Non-religious vs religious undergraduate subjects completed an experimental task that assessed levels of conformity in a domain unrelated to religion (i.e. in judgments of facial attractiveness). Findings showed that, although both groups yielded to conformity pressures at the self-report level, non-religious individuals did not yield to such pressures in their neural responses. These findings highlight a novel link between religiosity and social conformity, and hold implications for prominent theories about the psychological functions of religion.